Approximate Distributions of the Residual Self-Interference Power in Multi-tap Full-Duplex Systems - Abusabah, Ayman T. (2021)
In this letter, we investigate closed-form distributions to approximate the power of the residual Self-Interference (SI) due to: 1) uncanceled signals transmitted over multiple delay-taps, and 2) the presence of radio frequency and transceiver impairments, of an In-Band Full-duplex (IBFDX) wireless system. Starting with the distribution of the residual SI power for a single tap, we extend the analysis for multiple taps comparing two different solutions. The first one is based on the Welch-Satterthwaite (W-S) approximation, while the second is a moment-based approximation to an α-μ distribution. When compared to empirical results obtained by simulation, our work shows that the distribution of the residual SI power can be accurately represented by the W-S approximation when the uncertainty level of the fading in the different taps is low. However, for higher levels of uncertainty we show that the α-μ moment-based approximation is more accurate. A comparison between simulated and numerical results show the effectiveness of the proposed model.